Understanding Women’s Capital in The Speech Codes of Indonesian Army’s Wives Organization (Persit Kartika Chandra Kirana). - Prautami, Aryati; Dwiningtyas, S.Sos, MA, Dr. Hapsari (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Persit is organization consisted by Indonesian army wives. Membership in Persit is obliged and position in Persit influenced by rank and position of Persit’s husband. Many women are proud and wishes to become a member of Persit. Position in Persit determined by rank and position of husband deprives self of Persit members as a woman. This research attempts to look at how other capitals used by the wives of soldiers in interacting within the organization which focused on the husband's rank and position. Every woman has its capitals to participate in the group, is no exception Persit members who use the symbolic capital which is the rank of the husband. In Persit there must be other capitals that can be used by members Persit to be seen without the use of ranks and positions husband.The methods used on this research is qualitative methods with a critical ethnographic analysis. The theory and concepts used in this study is the Speech Codes Theory (SCT) by Philipsen, the concept of modalities by Bourdieu, and the concept of power and subjectivity by Foucault. The study found there are two capital are visible in Persit which is simbolic capital and social capital. In addition there are three codes are very visible in Persit which is codes of dignity, codes of loyalty and codes of power. Codes of dignity are used to indicate the position of the highest person in the group which can be seen through the language selection, how member Persit called other member. Codes of loyalty are used to demonstrate compliance a member Persit which see conversation topics tend to be avoided when talking with other members, the feeling when doesn't follow Persit activity and courage in expressing opinions.Codes of power are showing that assert authority in a bind Persit organization for its members to follow the activities of Persit and speak according to the position and rank of her husband. In all three of these codes Persit member, using the symbolic capital there is rank husband. Symbolic capital is very strong in the organization Persit which, although members Persit using another of its capital, but still Persit member positions as seen from the rank of the husband. The position and rank of the husband make Persit member, using social capital when interacting with members of other Persit member. This social capital is used for to maintain good relations with members of both Persit which is higher or equal. Persit members who use this social capital tend to avoid criticism or suggestions to members Persit which is higher than herself. Besides the position of members Persit can also be seen when she joined the management Persit. Persit member can use his ability in the arts / sports and work experience to be appointed as board Persit.